Pilot implementation study of a web-based men’s health screening app in primary care during COVID-19 : a mixed-methods approach - Ooi, Chor Yau; Ng, Chirk Jenn; Anne, Sales; Teo, Chin Hai (BioMed Central Ltd., 2024)
Background The traditional delivery of healthcare services, including crucial preventive measures such as health screenings, faced significant disruption due to the COVID-19 pandemic. In response, eHealth technology emerged as a practical alternative for conducting screening services. This pilot study introduces ScreenMen, a web-based app for men’s health screening, implemented in a primary care setting. The study aims to assess patient uptake and healthcare provider’s acceptability and feasibility of implementing ScreenMen, emphasizing the importance of implementation science research in healthcare innovation.